The Open Brethren: A Christian Sect in the Modern World - Herriot, Peter (Springer International Publishing, 2018)
This book gives a personal insight into the hearts and minds of a fundamentalist Christian sect, the Open Brethren. Using Brethren magazine articles, obituaries, and testimonies, Peter Herriot argues that the Brethren constitute a perfect example of a fundamentalism. Their culture is entirely opposed to the beliefs, values, and norms of modernity. As a result, like other fundamentalisms they challenge modern Christianity and impede its efforts to engage with global society.